Evaluación del potencial interpretativo en las rutas de excursionismo del Refugio de Vida Silvestre Pasochoa, cantón Mejía, provincia de Pichincha - Yachimba Oña, Jonathan Rodrigo (2022)
The Pasochoa Wildlife Refuge is a protected natural area that tourists use for various recreational activities; despite this, there is a lack of a baseline study on the interpretive resources, causes ignorance and lack of concern on the part of the authorities, surrounding communities, and visitors that stimulate the deterioration of these hiking trails, hence the need for this research work that was carried out in the Wildlife Refuge Pasochoa (RVSP), Mejía canton, Pichincha province, to establish the interpretative potential of the hiking trails through field study applying the IPI evaluation sheets. Based on this, an attempt was made to highlight the interpretative resources to inform the visitor of their existence and value. The natural resources were identified by characterizing the study area through primary and secondary sources and field visits to the six trails that were divided into two routes: three self-guided trails and three guided trails. The resources taken into account in the first route were: the Santa Ana creek, sword-billed hummingbird (Ensifera Ensiferum), orchids (Orchidaceae), long-tailed Zamarripa (Eriocnemis Luciani), paramo rabbit (Sylvilagus brasiliensis) and zuro (Chusquea scandens) and for the second route the resources were: the Mayguayacu viewpoint, Polylepis (Polylepis sp), Palma de ramos (Ceroxylon alpinum), paramo wolf (Lycalopex culpaeus), the caldera of the extinct Pasochoa volcano and Andean Condor. All these resources were evaluated through an adaptation of the sheet to determine the Interpretive Potential Index (IPI) (Lozano, 2015) (Morales & Varela, 1986), whose weighting was established in the range of 1–5 according to the nine evaluation criteria (Uniqueness, Attractiveness, Impact resistance, Accessibility, Seasonality, Current influx, Available information, Security, Adequacy). The second route (guided trails) obtained a better assessment of its natural resources with a higher degree of interpretive potential, whose total weight was 28.83/45 equivalent to a high (A), meaning that these resources have adequate features to be interpreted; however, the resources evaluated in the first route (self-guided trails) had a total weighting of 27.17/45 equivalent to medium-high (mA), which were only one degree apart since they have acceptable features for being interpreted. In conclusion, the environmental interpretation can be carried out on both routes, but having priority for the resources of the second route. Therefore, it is recommended to carry out a study that expands the information on them based on their care and conservation.